Viridantha, a new genus of Bromeliaceae (Tillandsioideae) endemic to Mexico - Espejo-Serna, Adolfo (Instituto de Ecología, A.C., 2002)
The genus Viridantha Espejo (Bromeliaceae) with two sections and six species, all endemic to Mexico and previously treated as Tillandsia, is proposed as new. Viridantha is characterized by the stamens equal in length, flat filaments and subbasifixed anthers, 2 - 4 mm long; ligulate, free, dark green petals; distichous, protandrous flowers; long asymmetric, densely to very densely disposed scales, and simple-erect stigmas (type I, sensu Brown & Gilmartin).